Close to Vermeer [videorecording (DVD)] - Roelofs, Pieter; Krekeler, Anna; Janson, Jonathan, 1950- (Kino Lorber, 2023)
Go behind the scenes of the largest Vermeer exhibition ever mounted, now on view at the Rijksmuseum in Amsterdam. Capturing the imagination of the art world, with glowing reviews, global press, and tickets sold out through the entirety of its run, the Rijksmuseum's Vermeer retrospective is nothing short of a historic event. This fascinating documentary is a unique opportunity to discover what goes on behind the scenes at exhibitions of this scale, from the latest techniques for determining what makes a Vermeer truly a Vermeer, to discoveries while searching for the master's paintings around the world.